ANALISIS REGRESI ALAT UKUR EMISI GAS KARBON MONOKSIDA BERBASIS ARDUINO UNO - Hasibuan, Azhari; Hakim, Lukman (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2020)
The presence of pollutants is a serious threat to health. One of the pollutants in influencing air quality is carbon monoxide gas. Most of the carbon monoxide comes from motor vehicle exhaust emissions. The purpose of this research is to make a vehicle carbon monoxide gas emission measurement tool using the TGS 822 gas sensor. The research method begins with the hardware design using the TGS822 gas sensor as a carbon monoxide gas sensor then processed with an arduino uno microcontroller and data transfer by bluetooth. The results of the reading of pollutant values ​​are then processed with a microcontroller and displayed on a computer screen using a Bluetooth connector so that it can be monitored in real time. Data obtained from the test results are then analyzed using a regression equation by comparing with data from the reading of standard measuring instruments. The results of testing the instrument shows the value of the regression equation y = -0,0641x ± 38.438 with a value of R2 = 0, 9997. These results show a strong correlation between the data from the CO meter with the CO gas emission gauge that has been made.